Investigating the effect of soil water constraints at different phenological stages of citrus trees to improve water use efficiency in the Sundays River Valley - Janse Van Rensburg, Christian (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.